2001
DOI: 10.2746/042516401776767377
|View full text |Cite
|
Sign up to set email alerts
|

Contact areas and pressure distribution on the proximal articular surface of the proximal phalanx under sagittal plane loading

Abstract: Summary The objective of this study was to map topographically contact areas and pressure distributions on the proximal articular surface (PAS) of the proximal phalanx (PI) under various clinically relevant loading conditions. Left and right forelimbs of 13 mature horses were transected halfway down the radius and loaded in a position mimicking the weightbearing attitude close to the midstance phase. Five loads were used which corresponded with loads that can be expected in different gaits or during athletic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
144
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(159 citation statements)
references
References 14 publications
14
144
1
Order By: Relevance
“…4,21 Different sites in a particular cartilage surface subjected to distinct loading patterns have different biochemical composition, [3][4][5] and the present study shows that there are also important differences in collagen structure between these sites: Irrespective of exercise group, there were significant differences in both parallelism and orientation of collagen fibrils between sites 1 and 2. PI was higher centrally (site 2) than peripherally (site 1), corresponding with marginal areas having a much larger transitional zone with more random fibril orientation than did central areas.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…4,21 Different sites in a particular cartilage surface subjected to distinct loading patterns have different biochemical composition, [3][4][5] and the present study shows that there are also important differences in collagen structure between these sites: Irrespective of exercise group, there were significant differences in both parallelism and orientation of collagen fibrils between sites 1 and 2. PI was higher centrally (site 2) than peripherally (site 1), corresponding with marginal areas having a much larger transitional zone with more random fibril orientation than did central areas.…”
Section: Discussionmentioning
confidence: 77%
“…1), which is constantly loaded during standing and during locomotion at all velocities but with peak loads substantially lower than at site 1. 4 …”
Section: Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a more extensive study into the topographical heterogeneity of the same articular surface, in which 12 sites were sampled and proteoglycan content was determined as well, it was demonstrated that there was a distinct and consistent topographical variation for all parameters determined: water, DNA, glycosaminoglycans, collagen, hydroxylysylpyridinoline (HP) cross-links and degree of lysyl hydoxylation (Brama et al 2000a). The findings corresponded neatly with the load distribution in the joint as determined using pressure-sensitive films in an in vitro setting and applying loads occurring during activities such as standing, walking, trotting, cantering and jumping (Brama et al 2001), showing that in the mature individual there is normally a match between loading and tissue characteristics, i.e. between the resistance of the tissue and the demands placed upon it.…”
Section: Articular Cartilagementioning
confidence: 99%